A Specific Analysis Of Service Quality Dimensions On Customer Satisfaction And Customer Loyalty: A Study Of Al-ijarah Thumma Al-bai' (Aitab) And Vehicle Financing-i (bai' Bithaman Ajil-bba) - Muhammad Ridhwan, Ab.Aziz; W Muhammad Zainuddin Wan Abdullah; Syadiyah Abdul Shukor (Global Biz Research, 2024)
Journal of Emerging Issues in Economics, Finance and Banking (JEIEFB) An Online International Monthly Journal (ISSN: 2306-367X) 2014 Vol: 3 Issue 2